REFERENCE CURVE FOR INDIAN ROLE MODEL SCIENTIST - Kalyane, V. L.; Madan, V. K.; Kumar, Vijai (Malaysian Journal of Library and Information Science, 2001)
A database on eminent Indian role model scientists (Homi Jehangir Bhabha, Pushpa Mittra Bhargav, Chittranjan R. Bhatia, Satyendra Nath Bose, Rajagopala Chidambaram, Virendra Lal Chopra, Padmanabha Krishnagopala Iyengar, Ramaswamy Hariharan Iyer, Shyam Sunder Kapoor, Kariamanikkam Srinivasa Krishnan, Prasanta Chandra Mahalanobis, L.L. Narayana, Jayant Vishnu Narlikar, Chandrashekhar Venkata Raman,Raja Ramanna, K. Ramiah, Ram Gopal Rastogi,G.M. Reddy, Vinodini Reddy, Meghnad Saha,Vikram Ambalal Sarabhai, Monkombu Sambasivan Swaminathan and C.S. Venkata Ram) was created with their number of publications during five-year periods starting from the first publication year, and it was processed for their central tendencies, in order to develop the quadratic equation employing:åYi = a n + b åXi + c åXi 2 , åXiYi = a åXi + b åXi 2 + c åXi 3; and åXi 2Yi = a åXi 2 + b åXi 3 + c åXi 4 ( where Xi and Yi are the observed year and cumulative publications respectively; and a, b, and c are constants of the fitted equation y=a+bx+cx2 ) to better fit a reference curve of expected values. Median values gave the best curve fit. Quinquenniumwise (Q) number of publications expected in the median of Indian role model scientist are:QI=11, QII=17, QIII=19, QIV=20, QV = 22, QVI =22, QVII=23, and QVIII=25.